Hyoliths and small shelly fossils from the Lower Cambrian of North-East Greenland - Malinky, John M.; Skovsted, Christian B. (Zenodo, 2004)
Malinky, John M., Skovsted, Christian B. (2004): Hyoliths and small shelly fossils from the Lower Cambrian of North-East Greenland. Acta Palaeontologica Polonica 49 (4): 551-578, DOI:10.5281/zenodo.13522197